Synthesis and Physico-Chemical Study of Supramolecular Compounds Sm and Gd (III) with Terephthalic Acid - Mammadova, S.R. (Herald of Azerbaijan Engineering Academy, 2022)
The paper provides newly synthesized complexes of samarium and gadolinium (III) with terephthalic acid examined by X-ray, elemental, IR spectroscopic and derivatographic analysis. Based on the results obtained, the chemical formulas of the complexes, the form of coordination of p-phtahalic acid, as well as the processes of thermal decomposition and the formation of isostructural supramolecular coordination compounds are established. It is also found that, despite the same compositions and structures, the thermal decomposition of these compounds is not lonely, which is explained by the nature of the metals and the stereochemistry of the ligands.